The spatial dynamics of homelessness in Australia 2001–11 - Wood, Gavin; Batterham, D.; Cigdem, M.; Mallett, S. (2014)
This is the first of two reports focusing on the structural factors underlying homelessness in Australia. This first stage details the analysis undertaken with large secondary data sources to examine the spatial dynamics of homelessness from 2001 to 2011. The second stage of the project, to be presented in a Final Report, will model the role of housing and labour markets, household income, and household characteristics in shaping the spatial distribution of homelessness across Australia. Australia has a rich bank of qualitative research that describes the circumstances, personal characteristics, and practices of people who experience homelessness. More recently research has investigated the pathways into and out of homelessness. However, to date there has been little investigation of the structural drivers of homelessness and minimal use of quantitative evidence to inform an understanding of the role that housing and labour market conditions play in shaping whether people are more or less vulnerable to homelessness.This project aims to fill this knowledge gap. In this report we address the following research questions: - Where is homelessness high and where is it low? - Where is homelessness rising or falling? - Is homelessness becoming more or less spatially concentrated? - Are there changes in the composition of the homeless population? - Are homelessness services well located to intervene in areas with high and rising rates of homelessness? - And finally, are changes in the geography of homelessness associated with changes in housing and labour market conditions, household income or other household characteristics? Following an increased national focus on homelessness, the Australian Bureau of Statistics has, for the first time, developed a statistical definition of homelessness that could be applied to multiple ABS census collections (2001, 2006, 2011), and for geographical units at different levels of aggregation. This recent development has enabled the current project to be undertaken.